Enhancing germination and seedling growth of barley using plasma-activated water (PAW) with neutralized pH - Mahmoud F. Seleiman; Nawab Ali; Emmanuely Z. Nungula; Harun I. Gitari; Bushra A. Alhammad; Martin L. Battaglia (Cogent Food & Agriculture)
Achieving the highest seed germination and seedling growth rates is of paramount importance to maximize overall crop productivity. Among different technologies aiming at increasing seed germination and early plant growth, cold atmospheric pressure plasma (CAP) and plasma-activated water (PAW) are two of the most promising. However, CAP has been shown to decrease the pH of water, potentially constraining the utility of PAW in applications involving pH-sensitive plants. Here, we assessed the impact of magnesium addition to PAW (Mg-PAW), a potential mitigator of water acidity, on barley germination and growth compared to CAP technology without Mg (PAW). Although seed germination increased with both treatments compared to just DI water (control), the increase was higher when Mg-PAW was added, increasing by 2.29 and 2.59 times on day 2 and day 3. Application of Mg-PAW also increased water absorption, seedling growth (both in terms of weight and length), concentrations of chlorophyll, carotenoids, total soluble protein and enzymatic activities compared to both the control and the PAW treatment. The Mg-PAW displayed a 1.8-fold higher total soluble protein level compared to PAW alone. Although both treatments reduced Malondialdehyde (MDA) content, a prominent stress marker in plants, Mg-PAW application resulted in a 46% higher reduction in MDA content than PAW alone. Also, Mg-PAW application increased superoxide dismutase (SOD) activity by 50%, and catalase (CAT) enzyme activity by 8% compared to PAW alone. The implications of these discoveries extend to different agricultural applications, offering a promising avenue for improved early plant growth using Mg-PAW technologies under neutral or near-to-neutral pH conditions.